494 Glycoprotein IIB/IIIA inhibitors may modulate the clinical benefit of radial access as compared to femoral access in primary percutaneous coronary intervention: a meta-regression and a meta-analysis of randomized trials. (8th December 2021) - Cristiano, Ernesto; Cava, Francesco; Monaco, Maria Lo; Tempestini, Federica; Giovannelli, Francesca; Tommasino, Antonella; Zardi, Domenico; Berni, Andrea; Volpe, Massimo
Abstract: Aims: Several randomized controlled trials (RCTs) consistently reported better clinical outcomes with radial as compared to femoral access for primary percutaneous coronary intervention (PCI). Nevertheless, heterogeneous use of potent antiplatelet drugs, such as Gp IIb/IIIa inhibitors (GPI), across different studies could have biased the results in favour of radial access. We performed an updated meta-analysis and meta-regression of RCTs in order to appraise whether the use of GPI had an impact on pooled estimates of clinical outcomes according to vascular access. Methods and results: We computed pooled estimates by the random effects model for the following outcomes: mortality, major adverse cardiovascular events (death, myocardial infarction, stroke, and target vessel revascularization), and major bleedings. Additionally, we performed meta-regression analysis to investigate the impact of GPI use on pooled estimates of clinical outcomes. We analysed 14 randomized controlled trials and 11 090 patients who were treated by radial (5497) and femoral access (5593), respectively. Radial access was associated with better outcomes for mortality [risk difference 0.01 (0.00, 0.01), P  = 0.03], MACE [risk difference 0.01 (0.00, 0.02), P  = 0.003], and major bleedings [risk difference 0.01 (0.00, 0.02), P  = 0.02]. At meta-regression, we observed a significant correlation of mortality with both GPI use ( P  = 0.011) and year of publication ( P  = 0.0073), whereas no correlation was observed with major bleedings. Conclusions: In this meta-analysis, the use of radial access for primary PCI was associated with better clinical outcomes as compared to femoral access. However, the effect size on mortality was modulated by GPI rate, with greater benefit of radial access in studies with larger use of these drugs.